1991
DOI: 10.1161/01.hyp.18.2.183
|View full text |Cite
|
Sign up to set email alerts
|

Sodium-lithium countertransport and hypertension in Rochester, Minnesota.

Abstract: The objectives of the present study were to determine whether increased sodium-lithium countertransport is associated with essential hypertension in the general Caucasian population and to determine whether this association is independent of the effects of gender, age, body size, and plasma lipids. We studied 543 men and 589 women from the population of Rochester, Minnesota. Mean sodium-lithium countertransport was higher in hypertensive than in normotensive subjects in men (370±147 [mean±SD] versus 315±110 jt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0
3

Year Published

1993
1993
2000
2000

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 44 publications
(24 citation statements)
references
References 22 publications
(16 reference statements)
1
20
0
3
Order By: Relevance
“…Recruitment and examination protocols have been described elsewhere. 6,7 From these pedigrees, 1569 full siblings distributed among 587 sibships and belonging to the youngest generation were identified. For a large proportion of the sibships (92%), both parents were available for genotyping.…”
Section: Subjectsmentioning
confidence: 99%
“…Recruitment and examination protocols have been described elsewhere. 6,7 From these pedigrees, 1569 full siblings distributed among 587 sibships and belonging to the youngest generation were identified. For a large proportion of the sibships (92%), both parents were available for genotyping.…”
Section: Subjectsmentioning
confidence: 99%
“…For instance, other groups have repeatedly shown that serum triglycerides correlated with the activity of the Na ϩ -Li ϩ exchange in erythrocytes and therefore modified the relationship between this transport system and blood pressure. [38][39][40][41][42] Our findings are relevant in that they clearly show that triglycerides do not modify the interrelationships between the various cellular Ca 2ϩ (and Na ϩ ) parameters but the relationships between these parameters and blood pressure. In this regard, the variation in lymphocyte parameters might not be causally related to variation in triglycerides.…”
Section: Resultsmentioning
confidence: 58%
“…The direct relationships of BMI and alcohol intake to Na-Li CT change are consistent with and extend cross-sectional findings. 1,4,16,17,22 The cumulative effects of BMI and alcohol intake were significant not only statistically; the combination of moderate differences in BMI and alcohol intake related to sizable differences in Na-Li CT change. The data support the concept that lifestyle influences Na-Li CT.…”
Section: Discussionmentioning
confidence: 94%